2015
DOI: 10.3171/2015.1.focus14785
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of traumatic injury to the craniovertebral junction: a case-based review

Abstract: OBJECT The craniovertebral junction (CVJ) is unique in the spinal column regarding the degree of multiplanar mobility allowed by its bony articulations. A network of ligamentous attachments provides stability to this junction. Although ligamentous injury can be inferred on CT scans through the utilization of craniometric measurements, the disruption of these ligaments can only be visualized directly with MRI. Here, the authors review the current literature on MRI eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Several studies have revealed issues with the reliability of image interpretation, as well as technical difficulties with patient positioning and image acquisition when performing these sequences [8,9,[11][12][13]33]. Lastly, this imaging technique may be inaccurate unless optimal technique is employed, necessitating expertise by involved staff [11,13,26]. These conflicting data highlight the need to investigate complementary imaging techniques which may reveal occult CCJ injury; additional methods of dynamic radiography, as described in this study, may provide that complement.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have revealed issues with the reliability of image interpretation, as well as technical difficulties with patient positioning and image acquisition when performing these sequences [8,9,[11][12][13]33]. Lastly, this imaging technique may be inaccurate unless optimal technique is employed, necessitating expertise by involved staff [11,13,26]. These conflicting data highlight the need to investigate complementary imaging techniques which may reveal occult CCJ injury; additional methods of dynamic radiography, as described in this study, may provide that complement.…”
Section: Discussionmentioning
confidence: 95%
“…The authors concluded that abnormal imaging findings did not correlate with symptoms and that there was no evidence to support the assertion that MRI reveals ligamentous injury in this patient population. Several studies have revealed issues with the reliability of image interpretation, as well as technical difficulties with patient positioning and image acquisition when performing these sequences [8,9,[11][12][13]33]. Lastly, this imaging technique may be inaccurate unless optimal technique is employed, necessitating expertise by involved staff [11,13,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergent spine CT as part of the initial advanced trauma life support (ATLS) evaluation has been shown to be much more reliable than standard radiographs to evaluate fractures and joint displacement [15, 16]. MRI may also be necessary to evaluate integrity of the soft tissues, spinal cord, or brainstem [4, 17]. MRI is especially critical in determining the integrity of the major ligamentous structures of craniocervical junction including the tectorial membrane, occipitocervical joint capsules, alar ligaments, and transverse ligament [7, 18].…”
Section: Discussionmentioning
confidence: 99%
“…This region is embryologically, anatomically, and biomechanically different from the other cervical region. [ 1 2 3 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%